An update of Africanization in honey bee (Apis mellifera) populations in Buenos Aires, Argentina - Genchi García, María Laura (2018)
European and African honey bee populations have been separated and influenced by different environments. Furthermore, Apis mellifera is the only species of honey bees that evolved in Europe, the Middle East, and Africa, where several subspecies are recognized. A. m. scutellata was introduced in Brazil in 1956, resulting in the spread of African bees throughout South and Central America. The aim of the present study was to determine the prevalence and geographical distribution of Africanized bees in Buenos Aires province (Argentina) employing a mtDNA cytochrome b polymorphism. A total of 430 colonies were sampled between 2013 and 2014; eighteen out of them (4,2%) belonged to African linage. Our results confirm that European haplotypes are the most prevalent in Buenos Aires Province, and that the process of African gene introgression remains stable since 2005.